PENGEMBANGAN VIDEO PEMBELAJARAN DIMENSI MANDIRI DAN BERGOTONG ROYONG BERBASIS PROFIL PELAJAR PANCASILA PADA SISWA SEKOLAH DASAR - Ary Purmadi; Menik Aryani; Diah Lukitasari (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2024)
The aim of this research is to develop independent and cooperative dimensions of learning videos based on Pancasila student profiles for elementary school children. The method used in this research is Research and Development (R & D). The results obtained were at the media testing stage (alpha testing), a result of 4.2 was obtained which was included in the good category. Furthermore, material testing obtained 4,6 results which were included in the very good category. At the student testing stage (beta testing), a result of 4,5 was obtained, which was included in very good category. So it can be stated that the development of learning videos for learning videos to stimulate the character of independence and mutual cooperation based on the Pancasila student profile is suitable for use. The contribution of this research is to provide examples of good practices that students can emulate through learning videos in everyday life.